Secondary School Library System:Fourth Plan Period - Sugra Begum, R. (Journal of Information and Knowledge, 2000)
This paper is based on the data for 1960-61, which are the latest available. Using the rate of increase in 1960-61, the secondary school enrolment and the number of library units needed during the Fourth Plan Period are calculated. An estimate is also made of the annual library fund and the strength of the library staff needed by the secondary schools in India during the Fourth Plan Period according to each of the four plan models. According to cheapest of these models, the annual library fund required for the secondary school library system in India is of the order of Rs 133 million for 1966-67 and Rs 380 million for 1970-71. The professional staff required is 4,220 and semiprofessional staff 86,510.